Oral Health Characteristics and Dental Rehabilitation of Children with Global Developmental Delay. (30th January 2017) - Kumar, Saurabh; Pai, Deepika; Saran, Runki
Abstract : Global developmental delay (GDD) is a chronic neurological disturbance which includes defects in one or more developmental domains. The developmental domain can be motor, cognitive, daily activities, speech or language, and social or personal development. The etiology for GDD can be prenatal, perinatal, or postnatal. It can be diagnosed early in childhood as the delay or absence of one or more developmental milestones. Hence the role of pedodontist and pediatricians becomes more crucial in identifying this condition. The diagnosis of GDD requires a detailed history including family history and environmental risk factors followed by physical and neurological examinations. Investigations for GDD include diagnostic laboratory tests, brain imaging, and other evidence-based evaluations. GDD affects multiple developmental domains that not only have direct bearing on maintenance of oral health, but also require additional behavior management techniques to deliver optimal dental care. This paper describes two different spectra of children with GDD. Since the severity of GDD can vary, this paper also discusses the different behavior management techniques that were applied to provide dental treatment in such children.